2022
DOI: 10.1038/s41467-022-35081-z
|View full text |Cite
|
Sign up to set email alerts
|

Increased fire activity under high atmospheric oxygen concentrations is compatible with the presence of forests

Abstract: Throughout Earth’s history, the abundance of oxygen in our atmosphere has varied, but by how much remains debated. Previously, an upper limit for atmospheric oxygen has been bounded by assumptions made regarding the fire window: atmospheric oxygen concentrations higher than 30–40% would threaten the regeneration of forests in the present world. Here we have tested these assumptions by adapting a Dynamic Global Vegetation Model to run over high atmospheric oxygen concentrations. Our results show that whilst glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Ancient ecosystems have been reconstructed using plant traits and included in models that make fire behavior predictions for time periods such as the Permian (He et al ., 2016), the Triassic–Jurassic (Belcher et al ., 2010; Belcher, 2016; Baker et al ., 2022), the Cretaceous (Belcher & Hudspith, 2017), and the Miocene (Boulton & Belcher, 2019). More recently, global dynamic vegetation models have been used to answer deep‐time questions regarding atmospheric oxygen that rely on consideration of plant functional types (Vitali et al ., 2022). Therefore, the study of fossil plant traits has a significant potential to inform novel understanding of paleo wildfires and their effects, and we have scored this trait highly as a paleo‐functional trait (7) accordingly (Table S1).…”
Section: Whole Plant Functional Traits Applied To Fossilsmentioning
confidence: 99%
“…Ancient ecosystems have been reconstructed using plant traits and included in models that make fire behavior predictions for time periods such as the Permian (He et al ., 2016), the Triassic–Jurassic (Belcher et al ., 2010; Belcher, 2016; Baker et al ., 2022), the Cretaceous (Belcher & Hudspith, 2017), and the Miocene (Boulton & Belcher, 2019). More recently, global dynamic vegetation models have been used to answer deep‐time questions regarding atmospheric oxygen that rely on consideration of plant functional types (Vitali et al ., 2022). Therefore, the study of fossil plant traits has a significant potential to inform novel understanding of paleo wildfires and their effects, and we have scored this trait highly as a paleo‐functional trait (7) accordingly (Table S1).…”
Section: Whole Plant Functional Traits Applied To Fossilsmentioning
confidence: 99%
“…The results of research obtained the range of smoldering combustion temperature of 500-700℃ which is lower than the flaming combustion (1500-1800℃) [6]. In the study of the effect of moisture and organic content as well as observed trends of smoldering combustion that could spread further and deeper laterally into the ground, revealed that fire activity would be greatly suppressed below 18.5% O2, completely switched off below 16% O2, and rapidly enhanced between 19-22% O2 [7]. There was significant influence of moisture content on the probability of smoldering combustion and the propagation rate of the tropical peat sample [8].…”
Section: Introductionmentioning
confidence: 99%